Mathematics and poetry: a travel around León de Greiff’s metrics (2017)
This study develops a sensitization with the theoretical technique of metric in order to understand the aesthetic proposal of Leon de Greiff’s poetics. In this case, we study the elements of the verse (syllabication, accentual rhythm, and ensemble) in his poem “Trova del cazador de efímeros arreboles”.